The Impact of Concomitant Medications on the Overall Survival of Patients Treated with Systemic Therapy for Advanced or Metastatic Renal Cell Carcinoma: A Systematic Review and Meta-analysis - Tsuboi, Ichiro; Matsukawa, Akihiro; Kardoust Parizi, Mehdi; Miszczyk, Marcin; Fazekas, Tamás; Schulz, Robert J; Mancon, Stefano; Litterio, Giulio; Laukhtina, Ekaterina; Kawada, Tatsushi; Katayama, Satoshi; Iwata, Takehiro; et al. (Clinical genitourinary cancer, 2024)
Although immune checkpoint inhibitors (ICI) and/or tyrosine kinase inhibitors (TKI) are the standard treatment of advanced unresectable or metastatic renal cell carcinoma (RCC), the impact of concomitant medications remains unclear. We aimed to evaluate the impact of concomitant medications on survival outcomes in patients treated with systemic therapy for advanced unresectable or metastatic RCC. In August 2024, PubMed, Scopus, and Web of Science were queried for studies evaluating concomitant medications in patients with advanced unresectable or metastatic RCC (PROSPERO: CRD42024573252). The primary outcome was overall survival (OS). A fixed- or random-effects model was used for meta-analysis according to heterogeneity. We identified 22 eligible studies (5 prospective and 17 retrospective) comprising 16,072 patients. Concomitant medications included proton pump inhibitors (PPI) (n = 3959), antibiotics (n = 571), statins (n = 5466), renin-angiotensin system inhibitors (RASi) (n = 6615), and beta-blockers (n = 1964). Both concomitant PPI and antibiotics were significantly associated with worse OS in patients treated with ICI (PPI: HR: 1.22, P = .01, and antibiotics: HR: 2.09, P < .001). Concomitant statins, RASi, or beta-blocker were significantly associated with improved OS in patients treated with TKI (statins: HR: 0.81, P = .03, RASi: HR: 0.63, P < .001, beta-blocker: HR: 0.69, P < .001, respectively). In patients treated with ICI, RASi was significantly associated with improved OS (HR: 0.64, P = .02). Concomitant use of antibiotics or PPI with ICI can reduce its oncologic efficacy. Conversely, concomitant statins, RASi, or beta-blockers can enhance the oncologic efficacy of TKI. When initiating systemic therapy for metastatic RCC, it may be important for clinicians to assess baseline co-medications and recognize their possible positive or negative effects.
Keywords: Immune checkpoint inhibitors; Adrenergic beta-Antagonists; analýza přežití; nádory ledvin; Immune Checkpoint Inhibitors; inhibitory protonové pumpy; lékové interakce; karcinom z renálních buněk; Chemotherapy; Hydroxymethylglutaryl-CoA Reductase Inhibitors; statiny; Kidney Neoplasms; beta blokátory; inhibitory proteinkinas; Survival Analysis; lidé; Humans; Drug Interactions; Protein Kinase Inhibitors; Concomitant medications metastatic renal cell carcinoma; inhibitory kontrolních bodů; Carcinoma, Renal Cell; Proton Pump Inhibitors